2004
DOI: 10.1002/mds.20006
|View full text |Cite
|
Sign up to set email alerts
|

Is the light chain subcellular localization an important factor in botulinum toxin duration of action?

Abstract: Botulinum neurotoxins (BoNT) are therapeutic proteins that are specific, potent, and effective. They are highly specific in binding to motor neurons but do not bind to other non-neuronal cells. These proteins are zinc-dependent endopeptidases that inhibit exocytosis by specific cleavage of the SNARE (soluble N-ethylmaleimide-sensitive factor-attachment protein-receptor) proteins involved in vesicle docking and fusion. The therapeutic effect of BoNT/A in humans lasts from 3 to 12 months, depending upon the cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Although earlier studies reported the intracellular localization of the LC of BoNT/A to the plasma membrane (21,22), the basis for plasma membrane association was not determined. Identification of a SNAP-25 interaction with the N terminus of LC/A was not expected because BoNT/A or LC/A was previously to bind and utilize SNAP-25(146 -206) as an efficient substrate for cleavage (13,15,28).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although earlier studies reported the intracellular localization of the LC of BoNT/A to the plasma membrane (21,22), the basis for plasma membrane association was not determined. Identification of a SNAP-25 interaction with the N terminus of LC/A was not expected because BoNT/A or LC/A was previously to bind and utilize SNAP-25(146 -206) as an efficient substrate for cleavage (13,15,28).…”
Section: Discussionmentioning
confidence: 98%
“…Membrane-inserted HCT facilitates LC translocation into the cytosol, where LC cleaves plasma membraneassociated SNAP-25 (18 -20). Although earlier studies reported the intracellular localization of ectopic expressed BoNT/A LC to the host plasma membrane (21,22), there is limited understanding of the intracellular events that lead to plasma membrane localization. In this study, a new interaction between LC/A and SNAP-25 is identified that facilitates high affinity binding of LC/A to SNAP-25 on the plasma membrane of neurons.…”
mentioning
confidence: 99%
“…Both of these proteases appeared to be dispersed throughout the cell, not localized to the plasma membrane [41,46]. These results suggest that localization to the plasma membrane is not required for protease persistence in these other long-lasting BoNT serotypes and their persistence depends on other mechanisms.…”
Section: Contribution Of Intraneuronalmentioning
confidence: 57%
“…BoNT protease subcellular localization to persistence-Because of the difficulties in detecting cytosolic BoNT protease following natural intoxication, several labs have employed DNA transfection methods to promote expression of the proteases within cells to study persistence [26,[39][40][41]. Fernandez-Salas et al over-expressed either recombinant BoNT/A or BoNT/E proteases within rat PC12 neuroblastoma cells as fusions to green fluorescent protein (GFP) and monitored protease localization by fluorescence microscopy.…”
Section: Contribution Of Intraneuronalmentioning
confidence: 99%
“…This has necessitated the transfection of plasmids encoding BoNT LCs that have been codon-optimized for mammalian expression to study BoNT persistence (12,(40)(41)(42). It is natural to ask whether discoveries based on transfection of BoNT LCs can be extended to intoxication with the holotoxin.…”
Section: Discussionmentioning
confidence: 99%